2015
DOI: 10.1007/s00441-015-2137-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of octopamine and tyramine receptors in Drosophila

Abstract: The monoamines octopamine and tyramine, which are the invertebrate counterparts of epinephrine and norepinephrine, transmit their action through sets of G protein-coupled receptors. Four different octopamine receptors (Oamb, Octß1R, Octß2R, Octß3R) and 3 different tyramine receptors (TyrR, TyrRII, TyrRIII) are present in the fruit fly Drosophila melanogaster. Utilizing the presumptive promoter regions of all 7 octopamine and tyramine receptors, the Gal4/UAS system is utilized to elucidate their complete expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
93
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 61 publications
12
93
0
Order By: Relevance
“…In the present study, we found that BdOctβR1 was highly expressed in adults and larvae, and a similar expression pattern of DmOctβR1 has been observed in D. melanogaster [15]. Based on these, we believe that our results suggest that octopamine might play an important role during the stages of larval and adult of B. dorsalis .…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, we found that BdOctβR1 was highly expressed in adults and larvae, and a similar expression pattern of DmOctβR1 has been observed in D. melanogaster [15]. Based on these, we believe that our results suggest that octopamine might play an important role during the stages of larval and adult of B. dorsalis .…”
Section: Discussionsupporting
confidence: 85%
“…VMA and MOPEG), as well as tyrosine derivatives such as tyramine and octopamine. Trace amines (tyramine, octopamine, tryptamine, and phenethylamine) play prominent roles in many invertebrate species [3640], and are present as metabolic by-products in the mammalian central nervous system, where they may neuromodulate biogenic amine signaling [40, 41]. Serotonin is derived from tryptophan, so several intermediates in tryptophan metabolism were included (Supplemental D).…”
Section: Resultsmentioning
confidence: 99%
“…Orthologs of OAMB have subsequently been identified in Apis (Blenau and Baumann, 2001;Grohmann et al, 2003;Balfanz et al, 2014), Anopheles (Kastner et al, 2014), Schistocerca (Verlinden et al, 2010b), and Locusta (Hiripi et al, 1994;Ma et al, 2015), among other invertebrate species. Whether the OAMB receptor is a true OCT receptor or a mixed OCT/TYR receptor has been a matter of some recent conjecture (El-Kholy et al, 2015). Very recently, a putative novel receptor with homology to a 2 -adrenoceptors was reported in Drosophila, coupled to G i -mediated inhibition of adenylyl cyclase, and activated by both OCT and TYR (Qi et al, 2017).…”
Section: Octopamine Receptorsmentioning
confidence: 99%
“…Subsequent to the OAMB receptor discovery, three further invertebrate OCT receptors were identified (Oct1bR, Oct2bR, and Oct3bR; Evans and Maqueira, 2005;El-Kholy et al, 2015), with strong homology to the vertebrate b 1-3 adrenergic receptors, respectively . Like their vertebrate counterparts, all three b-receptors are coupled to the cAMP signal transduction cascade through activation of adenylyl cyclase (Chang et al, 2000;Maqueira et al, 2005;Balfanz et al, 2014).…”
Section: Octopamine Receptorsmentioning
confidence: 99%